Oh, Otto! - Morgan, Michaela (Oxford Oxford University Press, 2014)
Meet Otto, a boy from outer space, in Oh, Otto!. 'There is a new boy coming today and he comes from far, far away,' Miss Underwood tells Class Four. Are Charlie, Josh and Jo ready to meet Otto? TreeTops Fiction contains engaging novels from top authors and illustrators with the variety children need to develop a love of reading!
Include Illustrations
Keywords: Schools -- Conduct of life -- Friendship